Alterações tecnológicas e químicas de grãos de feijão carioca durante o armazenamento em condições controladas - Almeida, Ana Julia Bispo de (2016)
Beans (Phaseolus vulgaris L.) are traditional in human diet since they show low fat, high contents of vitamins, protein, fiber, carbohydrates and minerals. It is present in Brazilians meals wherever you go in Brazil and it is consumed in all social classes. However, one of the main problems with this product is the long storage term, whose temperature and humidity control have not been carried correctly out, consequently, there is a decrease on these grains quality. Thus, this study aimed at identifying technological and chemical changes in the grains of common bean cultivars during the storage term under controlled temperature and humidity conditions. Four varieties of grains as carioca group, BRS Madrepérola, BRS Estilo, BRS Pontal and CNFC 10467, patentable by Embrapa, were stored in hermetic acrylic containers. Humidity was controlled by saturated salt solutions, while, in oreder to control temperature, the grains were placed in a controlled temperature chamber, BOD type. It was found out that BRS Madrepérola variety was superior regarding the brightness color parameter when compared to the other studied varieties. The storage condition was the factor that most influenced the color difference in grains. Factors as storage conditions and storage term have influenced the increase on cooking time; and the interaction of both factors showed a combined effect on increasing cooking time for all studied varieties. The grains stored under 27 °C and 75% humidity conditions and at 108 days have also shown a Hard-to-Cook effect characteristic. These studied factors did not show significant effects on phytate content value. Although, the storage period has shown a negative effect on phosphorus content of the studied varieties. BRS Pontal variety was the most different from the other studied ones. And varieties as CNFC 10467 and BRS Madrepérola were more similar, as the parameters examined